An Opto-Structural Method to Estimate the Stress-Strain Field Induced by Cell Contraction on Substrates of Controlled Stiffness in Vitro. Issue 3 (September 2013) - Raimondi, Manuela Teresa; Balconi, Giovanna; Boschetti, Federica; Di Metri, Antonio; Mohammed, Salman Afroze Azmi; Quaglini, Virginio; Araneo, Lucio; Galvéz, Beatriz G.; Lupi, Monica; Latini, Roberto; Remuzzi, Andrea
Purpose: Mechanical properties of the extra-cellular matrix (ECM) such as stiffness mediate cell signaling, proliferation, migration, and differentiation. Within this context, we developed a method to estimate in vitro the stress-strain field induced by contraction of cardiovascular progenitor cells on substrates of controlled stiffness. Methods: Two alginate-agarose hydrogels were polymerized and mechanically characterized under compression. The hydrogels showed different levels of stiffness, mimicking either normal or pathologic ECM of the cardiac tissue, with an average compressive equilibrium modulus of 3 and 25 kPa, respectively. To estimate substrate deformation induced by the adhering cells, fluorescent microspheres were included under the surface layer of the hydrogels as displacement trackers. The hydrogels were polymerized in multiwell plates and seeded with cells that were allowed to adhere for 24 hours. On the softer substrate, images of the substrate surface and the cells were acquired using time-lapse fluorescence microscopy. Image processing enabled tracking the microsphere movements and mapping local substrate deformation because of tensile stresses produced by the cells. The resulting tensile stresses could then be calculated from measured stiffness. Results and Conclusions: The substrate strains ranged between a maximum contraction of –26.5% to a maximum stretching of 19.8%. The calculated stresses ranged between a maximum compression of –0.53 kPa to a maximum tension of 0.4 kPa (nN/μm 2 ). These results may help to interpret experimental findings, showing important differences in cell morphology and expression of phenotypic markers, induced by culturing cells on substrates with different mechanical properties.